Religious Involvement and Adaptation in Female Family Caregivers. Issue 3 (March 2016) - Koenig, Harold G.; Nelson, Bruce; Shaw, Sally F.; Saxena, Salil; Cohen, Harvey Jay
Abstract : Objectives: To examine the relationship between religious involvement (RI) and adaptation of women caring for family members with severe physical or neurological disability. Design: Two‐site cross‐sectional study. Setting: Community. Participants: A convenience sample of 251 caregivers was recruited. RI and caregiver adaptation (assessed by perceived stress, caregiver burden, and depressive symptoms) were measured using standard scales, along with caregiver characteristics, social support, and health behaviors. Bivariate and multivariate analyses were conducted to identify relationships and mediating and moderating factors. Results: Religious involvement (RI) was associated with better caregiver adaptation independent of age, race, education, caregiver health, care recipient's health, social support, and health behaviors (B = −0.09, standard error = 0.04, t = −2.08, P = .04). This association was strongest in caregivers aged 58–75 and spouses and for perceived stress in blacks. Conclusion: Religious involvement (RI) in female caregivers is associated with better caregiver adaptation, especially for those who are older, spouses of the care recipients, and blacks. These results are relevant to the development of future interventions that provide support to family caregivers.